2015
DOI: 10.3352/jeehp.2015.12.41
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of burnout syndrome with specific coping strategies, behaviors, and spiritual attitudes among interns at Yale University, New Haven, USA

Abstract: Purpose:This study aimed to determine the correlation of burnout syndrome with specific coping strategies, behaviors, and spiritual attitudes among interns in internal medicine, primary care, and internal medicine/pediatrics residency programs at two institutions.Methods:Intern physicians completed anonymous voluntary surveys prior to starting the internship in June 2009 and in the middle of the internship in February 2010. Three validated survey instruments were used to explore burnout, coping, and spiritual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
2
28
1
5
Order By: Relevance
“…As stated previously, research highlighted the positive role of workplace spirituality in the promotion of employee well-being [34][35][36][59][60][61]. However, very few studies considered its effects on burnout [41,42,[62][63][64][65]. Nevertheless, this topic seems relevant because the burnout syndrome is a serious threat to health [66]: it was recently included in the International Classification of Diseases, 11 th revision, by the World Health Organization (ICD-11) [67].…”
Section: Studymentioning
confidence: 99%
“…As stated previously, research highlighted the positive role of workplace spirituality in the promotion of employee well-being [34][35][36][59][60][61]. However, very few studies considered its effects on burnout [41,42,[62][63][64][65]. Nevertheless, this topic seems relevant because the burnout syndrome is a serious threat to health [66]: it was recently included in the International Classification of Diseases, 11 th revision, by the World Health Organization (ICD-11) [67].…”
Section: Studymentioning
confidence: 99%
“…In their 2 survey-based studies of internal medicine housestaff, Doolittle et al found that high scores on the Hatch Spiritual Involvement and Beliefs Scale were correlated with lower self-identified burnout. 42,43 Although data specifically pertaining to the ICU are scarce, Meltzer and Huckabay reported that religiosity was protective against burnout in critical care nurses. 44 As such, tending to health-care workers’ spiritual health and spiritual needs may be important in preventing emotional exhaustion in the ICU.…”
Section: Spiritual Care Needs Of Health-care Workersmentioning
confidence: 99%
“…3 Maslach and her colleague 5,6 have studied the burnout syndrome for many years and devised a measurement tool-the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). 4,7 Although some studies of burnout have been conducted among dentists using the MBI-HSS, 1,[8][9][10] most studies on stress and burnout in health professions have focused on physicians [11][12][13] and nurses. 14,15 In 2001, a survey was conducted to investigate the sources of occupation stress among dentists in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%